Alteration of synthetic basaltic glass in silica saturated conditions: Analogy with nuclear glass. (October 2018) - Ducasse, T.; Gourgiotis, A.; Pringle, E.; Moynier, F.; Frugier, P.; Jollivet, P.; Gin, S.
Abstract: This study investigates the analogy between basaltic and borosilicate glasses of nuclear interest, by focusing on mechanisms controlling glass dissolution under silica saturation conditions. These conditions are representative of a non- or slowly renewed contacting solution, favouring the formation of a potentially passivating silica rich gel layer and secondary phases. Laboratory batch experiments were performed with synthetic basaltic glass altered at 90 °C, at pH 7 in a saturated 29 Si-doped aqueous solution for more than 600 days. Using elemental and isotopic solution analysis and solid characterizations by SEM, TEM and ToF-SIMS, we show that basaltic glass corrodes at an unexpectedly high and constant dissolution rate of 4 × 10 −3  g m −2  d −1 associated with the absence of passivating gel. Our results highlight the fact that the dissolution rate is controlled by the hydrolysis of the glassy network, sustained by the precipitation of clay-type minerals and amorphous silica. When tested in similar conditions, the International Simple Glass (ISG), a six oxide borosilicate glasses of nuclear interest displays a much lower rate limited by water diffusion through a passivating layer. The different behavior of the two glasses is explained by their ability to form secondary crystalline phases at the expense of an amorphous passivating film. Highlights: Alteration of synthetic basaltic glass is studied under Si saturation conditions. The rate is controlled by matrix dissolution driven by secondary phases formation. Comparison is made with borosilicate of nuclear interest. Significant differences are evidenced.